(3GddBdj aj TQM CeGdj GdbGdjs - (3CHhYHjO YHO Gddg Hf YHO GdYRjR Hf eMeO GdHcQj GdCfOdSjs; (3CHh Ydj GdbGdj , ESeGYjd Hf GdbGSe Hf YHOhf Hf gGQhf Hf YjSi Hf eMeO Hf SdeGf, CHh Ydj,J (B356 (3g` s
(3ChdgG (B:s
(3bGd CHhYHjO GdMeO ddg MeOkG jbJVj QVGg gPG cJGH TQMJ ajg ef GdfhGOQ GdJj CHhYdi ESeGYjd Hf GdbGSe GdbGdj eG CZad s
(3BNQgG (B:s
(3EPG eG LdSfG dG JRGd JQhefG Jeje dOi CHjGJfG hghGRf GfJgi GdehLhO ef TQM CeGdj CHj Ydi GdbGdj s
(3GdNW ajg VHWs
(3fSNI Chdis
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs